Korelasi Usia Metabolik terhadap Indeks Massa Tubuh - Ni Nyoman Sri Yuliani; Elsa Trinovita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Excessive fat accumulation in the body causes an increase in Body Mass Index (BMI). Increased BMI and comorbidities affect the metabolic rate. Metabolic age was influenced by the individual metabolic rate. The purpose of this study was to determine the description of metabolic age to BMI increasement. This cross-sectional study used a purposive sampling method to obtain 82 male and female subjects. Subjects were measured for BMI and metabolic age. Collected data was analyzed univariately and bivariate correlatively. The result showed a significant correlation between metabolic age and BMI (p = 0,001) with r = 0,812. The conclusion of this study is the increase in BMI, the higher the metabolic age.